Implicit form-focused instruction: The impact on the implicit and explicit knowledge of Malaysian ESL learners - Majid Hojjat; Zuwati Hasim (Indonesian Journal of Applied Linguistics, 2023)
Considering that previous research had predominantly focused on explicit FFI as the preferred method to enhance explicit and implicit knowledge, This study examined the impact of implicit form-focused instruction (FFI) on learners’ explicit and implicit knowledge. This quasi-experimental study was conducted at a selected international school in Malaysia, with 30 participants divided into two intact groups: an experimental group and a control group, each comprising 15 participants. The explicit and implicit knowledge of learners were assessed utilizing four tests: Elicited Oral Imitation Test (EOIT), Timed Grammatical Judgment Test (TGJT), Untimed Grammatical Judgment Test (UGJT), and Metalinguistic Knowledge Test (MKT). ANCOVA and Scheffe’s tests were used to analyse the obtained data. The findings demonstrated that implicit FFI, like applying input enhancement techniques and recasting, significantly affected learners’ implicit and explicit knowledge. This finding suggests that learners do not need to improve explicit knowledge to enhance their implicit knowledge. Therefore, the significant role of implicit FFI in second language acquisition (SLA) should not be underestimated. Thus, teachers could consider the effectiveness of implicit FFI when crafting impactful lessons that consider implicit and explicit knowledge. Also, this study has provided reliable support indicating that L2 learners would substantially benefit from pedagogical activities, such as input enhancement and recasting.